Konseling Keluarga untuk Mengatasi Kesehatan Mental Anak - Wahyu Gunawan Lubis; Sri Nurdayang; Dika Syahputra (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The family is the first and foremost institution for family members to socialize, this is where family members know love, sympathy and get guidance and education and feel a safe atmosphere. Healthy realization with all family members is very important because the family is the one we can trust to talk about a problem, the burden of the problems we face. Where if we bury all our own problems will interfere with the mind or mental health. The family directly or indirectly determines the formation of character or personality or other family members. For example, the behavior of parents who are temperamental, likes to get drunk with explosive emotions, the occurrence of rifts between parents can cause inner conflicts for their children, the rule method is used in a qualitative method of literature review where researchers seek discussion. bring back a new title with literature review literature. The technique of checking the validity of knowledge is by using a literature review. The results of this study indicate that most children's mental health is good, only that some children experience stress or mental health disorders in the family, family counseling to overcome children's mental health is very important. thus families can educate children so that there is no lack of mental health in children. Keywords: family counseling, mental, children